Plasmacytoid Dendritic Cell Infection and Sensing Capacity during Pathogenic and Nonpathogenic Simian Immunodeficiency Virus Infection - Jochems, Simon P; Jacquelin, Beatrice; Chauveau, Lise; Huot, Nicolas; Petitjean, Gaël; Lepelley, Alice; Liovat, Anne-Sophie; Ploquin, Mickaël J; Cartwright, Emily K; Bosinger, Steven E; Silvestri, Guido; Barré-Sinoussi, Françoise; et al. (Journal of virology, 2015)
Human immunodeficiency virus (HIV) in humans and simian immunodeficiency virus (SIV) in macaques (MAC) lead to chronic inflammation and AIDS. Natural hosts, such as African green monkeys (AGM) and sooty mangabeys (SM), are protected against SIV-induced chronic inflammation and AIDS. Here, we report that AGM plasmacytoid dendritic cells (pDC) express extremely low levels of CD4, unlike MAC and human pDC. Despite this, AGM pDC efficiently sensed SIVagm, but not heterologous HIV/SIV isolates, indicating a virus-host adaptation. Moreover, both AGM and SM pDC were found to be, in contrast to MAC pDC, predominantly negative for CCR5. Despite such limited CD4 and CCR5 expression, lymphoid tissue pDC were infected to a degree similar to that seen with CD4(+) T cells in both MAC and AGM. Altogether, our finding of efficient pDC infection by SIV in vivo identifies pDC as a potential viral reservoir in lymphoid tissues. We discovered low expression of CD4 on AGM pDC, which did not preclude efficient sensing of host-adapted viruses. Therefore, pDC infection and efficient sensing are not prerequisites for chronic inflammation. The high level of pDC infection by SIVagm suggests that if CCR5 paucity on immune cells is important for nonpathogenesis of natural hosts, it is possibly not due to its role as a coreceptor. The ability of certain key immune cell subsets to resist infection might contribute to the asymptomatic nature of simian immunodeficiency virus (SIV) infection in its natural hosts, such as African green monkeys (AGM) and sooty mangabeys (SM). This relative resistance to infection has been correlated with reduced expression of CD4 and/or CCR5. We show that plasmacytoid dendritic cells (pDC) of natural hosts display reduced CD4 and/or CCR5 expression, unlike macaque pDC. Surprisingly, this did not protect AGM pDC, as infection levels were similar to those found in MAC pDC. Furthermore, we show that AGM pDC did not consistently produce type I interferon (IFN-I) upon heterologous SIVmac/HIV type 1 (HIV-1) encounter, while they sensed autologous SIVagm isolates. Pseudotyping SIVmac/HIV-1 overcame this deficiency, suggesting that reduced uptake of heterologous viral strains underlays this lack of sensing. The distinct IFN-I responses depending on host species and HIV/SIV isolates reveal the host/virus species specificity of pDC sensing.